(untitled) (Islas, 2024)
Introduction: The research delves into the history of the parish cemetery of Santo Cristo del Buen Viaje in the former town of Puerto Príncipe, from its establishment in 1790 to its transformation into a General Cemetery in 1814. Methods: Theoretical and empirical methods were used for this article, which allowed for an in-depth chronological analysis of the parish cemetery and systematization of existing information through primary sources, as well as the identification of aspects related to its evolution. Results: The study deepened the understanding of the emergence, evolution, and functioning of the parish cemetery of Santo Cristo del Buen Viaje in the former town of Puerto Príncipe, covering the period from its founding to its conversion into a general cemetery—topics that had been scarcely addressed by local historiography. Conclusions: The research provided a deeper understanding of the origins, functioning, and evolution of the parish cemetery of Santo Cristo del Buen Viaje in the town of Puerto Príncipe, from its establishment in 1795 to its transformation into a general cemetery, taking into account data that demonstrated its acceptance and assimilation.